Observation of the Effects of Infrapatellar Fat Pad Excision on the Inflammatory Progression of Knee Osteoarthritis in Mice - Li Y; Lu P; Yao H; Yang S; Tu B; Kong L; Ning R (Journal of Inflammation Research, 2025)
Ya Li,1,2,* Peizhi Lu,1,2,* Haoyu Yao,2 Shuo Yang,2 Bizhi Tu,2 Lingchao Kong,2 Rende Ning1,2 1Graduate School, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China; 2Department of Orthopedics, The Third Affiliated Hospital of Anhui Medical University, The First People’s Hospital of Hefei, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingchao Kong, Department of Orthopedics, The Third Affiliated Hospital of Anhui Medical University, The First People’s Hospital of Hefei, Hefei, Anhui, People’s Republic of China, Tel +86 13956910088, Email konglingchaocn@163.com Rende Ning, Graduate School, Bengbu Medical University, Bengbu, Anhui, People’s Republic of China, Tel +86 13956966305, Email nrd1972@outlook.comBackground: Knee osteoarthritis (KOA) is a degenerative joint disease characterized by cartilage degradation, synovial inflammation, and joint pain. The infrapatellar fat pad (IFP) has been suggested to play a role in modulating the inflammatory processes in KOA. Excision of the IFP is considered a potential therapeutic approach to reduce inflammation and slow disease progression.Methods: A mouse model of KOA was used to evaluate the impact of IFP excision on inflammation. Mice were divided into five groups: sham (control), unexcised IFP, quarter excision, partial excision, and complete excision of the IFP. Knee joints were collected at early, middle, and late stages of KOA. Gait analysis, micro-computed tomography (micro-CT), HE staining, Safranin O-Fast Green staining, and immunohistochemistry (IHC) were performed to assess joint stability, bone changes, and inflammatory markers (MMP-3, IL-6, TNF-α, COL-2). qRT-PCR was conducted for cartilage tissue analysis.Results: Partial IFP excision significantly improved joint stability, particularly in the middle and late stages of KOA. Micro-CT analysis showed increased bone volume fraction (BV/TV) and trabecular thickness (Tb.Th) in excised groups, with the most significant effects in the partial and complete excision groups. IHC and qRT-PCR indicated reduced MMP-3, IL-6, and TNF-α levels in excised groups, particularly in the partial and complete excision groups, suggesting reduced inflammation. COL-2 expression was higher in excised groups, particularly in late-stage KOA, indicating cartilage protection. The partial excision group exhibited the most balanced reduction in inflammation and improved cartilage integrity across all disease stages.Conclusion: IFP excision, especially partial excision, significantly modulates the inflammatory response in KOA. Partial excision showed the most effective and balanced impact on joint stability, bone integrity, and cartilage protection, offering potential as a therapeutic approach for KOA.Keywords: knee osteoarthritis, infrapatellar fat pad, inflammation, micro-CT, mouse model